6 - Moving beyond Poststructural Paralysis: Articulating an Ethic of Diaspora Collaboration - Nkhoma, Nelson Masanche (Journal of Higher Education in Africa, 2022)
Scholars in African higher education agree on the importance of collaboration with scholars in the diaspora. Despite this agreement, two major obstacles affect the implementation of collaboration: the politics of identity and difference and the common view of ethics as power. Literature on diaspora and collaborations tends to gloss over fundamental issues on the ethics of collaborations. In this article I reflect on how these two points of paralysis can be overcome by adopting an African humanist ethic that can drive the building of functional institutions to foster collaboration between and among scholars in Africa and those in diaspora. The article argues that in order to contribute to meaningful development in Africa, scholars need to move beyond the politics of identity and ethics as oppressive power.